2004
DOI: 10.1074/jbc.m313778200
|View full text |Cite
|
Sign up to set email alerts
|

The Mammalian Exocyst, a Complex Required for Exocytosis, Inhibits Tubulin Polymerization

Abstract: The exocyst is a 734-kDa complex essential for development. Perturbation of its function results in early embryonic lethality. Extensive investigation has revealed that this complex participates in multiple biological processes, including protein synthesis and vesicle/ protein targeting to the plasma membrane. In this article we report that the exocyst may also play a role in modulating microtubule dynamics. Using monoclonal antibodies, we observed that endogenous exocyst subunits co-localized with microtubule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
66
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 31 publications
6
66
0
1
Order By: Relevance
“…There is no information regarding an involvement of BIG2 in these processes. Exo70 was found to induce depolymerization of microtubules in vitro (25), but similar action in mitotic cells has apparently not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no information regarding an involvement of BIG2 in these processes. Exo70 was found to induce depolymerization of microtubules in vitro (25), but similar action in mitotic cells has apparently not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that only Exo70-GFP appeared confined to the lateral plasma membrane, although it was not localized like the endogenous protein, and it failed to generate tight intercellular contacts. Wang et al (25) found that overexpression of GFP-Exo70 (but not GFP-Exo84) resulted in the disruption of microtubule architecture in the area of cytoplasm under regions of plasma membrane protrusions, and microtubule polymerization in vitro was inhibited by recombinant Exo70. The interaction of BIG2 with Exo70 in these processes suggests a mechanism for the congenital defects described in two families with mutations in the BIG2 gene (7).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of phospholipase D2 impaired L1-stimulated neurite outgrowth in cerebellar granule neurons [95]. The exocyst refers to a 734 kDa complex, consisting of at least eight subunits, that is required for exocytosis [94]. RalA is also associated with refilling the readily releasable pool (RRP) of synaptic vesicles [77], and has been shown to bind to the actin-binding protein filamin and thereby induce formation of filopodia [69].…”
Section: Gap-43 G Proteins Small Gtpases and Filopodiamentioning
confidence: 99%
“…As shown in Figure 1A, GFP-Exo70 was clearly detected at the PM as revealed by serial optical sectioning from different axis ( Figure 1A). In addition, cells expressing GFP-Exo70 displayed filopodia-like structures as previously reported (Wang et al, 2004;Xu et al, 2005;Zuo et al, 2006). We next mapped the region of Exo70 that is required for its association with the PM by examining the localization of a series of GFP-tagged Exo70 truncates in HeLa cells.…”
mentioning
confidence: 99%